Assessing the unmet need for modern contraceptives among reproductive-aged women in rural Nepal - Samyukta Chand; Kanittha Chamroonsawasdi; Paranee Vatanasomboon; Natkamol Chansatitporn (Journal of Health Research, 2022)
Purpose – The purpose of this research was to determine the extent of the unmet need for modern contraceptives (MC) and its associated factors. Design/methodology/approach – This community-based cross-sectional survey was conducted via interview among 306 women. Percentages, means, standard deviations, Chi-square tests and multiple logistic regression were completed for data analysis. Findings – In total, 46.7% of respondents had total unmet need (24.8% spacing and 21.9% limiting). Multiple logistic regression for spacing showed the number of living children (AOR = 40.893, 95% CI = 6.930–241.292), no previous experience of MC (AOR = 30.149, 95% CI = 11.572–78.548) and level of knowledge (AOR = 5.587, 95% CI = 1.366–22.851). With regard to limiting pregnancies, respondent's age (AOR = 12.470, 95% CI = 1.264–86.734), number of living children (AOR = 21.257, 95% CI = 4.825–93.639) and no previous experience of MC (AOR = 120.542, 95% CI = 31.044–486.062) were recorded. Findings revealed that no previous experience of MC (AOR = 714.511, 95% CI = 160.646–3177.955) was a significant predictor of total unmet need. Originality/value – Experience and knowledge of MC play a vital role in the unmet need of MC use. A comprehensive education program to promote decision-making on MC choice and integrated family planning services at local communities by capacity building of service providers should be scaled up.